Filmowe adaptacje „Straconej nocy” Jarosława Iwaszkiewicza – analiza porównawcza - Dąbrowska, Dorota (Załącznik Kulturoznawczy, 2024)
The aim of this article is a comparative analysis of three film adaptations of Jarosław Iwaszkiewicz’s short story Stracona noc (en. Lost Night) – a fragment of the film Spotkania (en. Meetings) by Stanisław Lenartowicz (1957), Stracona noc by Janusz Majewski (1973) and Nocne ptaki (en. Night Birds) by Andrzej Domalik (1992). Focusing on the perspective of reflection on the ways in which the motifs contained in the original text are equivalent, I aim to demonstrate the significant differentiation between the meanings conveyed by the analyzed films.